Penerapan K3 (Keselamatan dan Kesehatan Kerja) Pada Bangunan Gedung Di Daerah Istimewa Yogyakarta - Afredo Tubur, Hasi; Sari, Sely Novita; Hermawan, Anggi (ReTII, 2023)
In the Special Region of Yogyakarta, the central hub of government, economy, and industry constitutes essential elements with diverse infrastructure and resources. Nevertheless, construction projects in this area often pose high risks to occupational safety and health. This situation has led to a poor safety record within the construction sector. To address this issue, efforts have been implemented in the form of Occupational Safety and Health (OSH) measures on construction projects, aiming to create a safer, healthier, and more productive work environment. This study examines the application of OSH on building construction projects in the Special Region of Yogyakarta, utilizing a quantitative field research method and questionnaires as primary data sources. The research findings indicate that the overall implementation of OSH on these projects is relatively good, with a lower standard deviation compared to the means of independent (X) and dependent (Y) variables. Variable X2 shows a positive influence on Y, while X1 and X3 do not exhibit significant positive effects. In summary, the independent variables collectively have a positive influence on the dependent variable, with a 53% impact.